Mediating Voices, Communicating Realities: Using Information Crowdsourcing Tools, Open Data Initiatives and Digital Media to Support and Protect the Vulnerable - and Berdou, Evangelia (IDS, 2011)
This is the final report from a research project, supported by the UK Department for International Development, examining whether and how open ICT projects designed to support the poor can make a diff...